Systematic review and meta-analysis of pentahelix partnerships in regional elite sport development - Bacilius Sukadana; Fadli Ihsan (Lentera Negeri, 2026)
This study aims to systematically review and meta-analyze empirical research on five-pillar partnership strategies in regional elite sport development, focusing on their effects on elite sport performance, governance effectiveness, and athlete development and wellbeing outcomes. Materials and Methods: A systematic review and meta-analysis were conducted following the PRISMA 2020 guidelines. Peer-reviewed empirical studies published between 2020 and 2025 and indexed in Scopus or higher were retrieved from Scopus, Web of Science, SPORTDiscus, and PubMed. Data were extracted regarding partnership configurations, outcome measures, and effect sizes. A random-effects meta-analytic model using Hedges’ g was applied to account for contextual heterogeneity across regions and sport systems. Results: The meta-analysis revealed a small-to-moderate positive effect of partnership-based strategies on elite sport performance (Hedges’ g = 0.34; 95% CI: 0.21–0.47; I² = 62%). Governance outcomes demonstrated the strongest effects, with a moderate pooled effect size (Hedges’ g = 0.48; 95% CI: 0.33–0.63; I² = 55%), indicating improved coordination, role clarity, and planning consistency. Athlete development and wellbeing outcomes showed a small but meaningful positive effect (Hedges’ g = 0.29; 95% CI: 0.15–0.43; I² = 68%), particularly in dual-career support and athlete retention. Conclusion: Five-pillar partnership strategies positively contribute to regional elite sport development, primarily by strengthening governance capacity and support structures rather than functioning as direct performance drivers. Their effectiveness depends on participatory governance, balanced stakeholder roles, and the integration of athlete-centered objectives.